Shifting norms and expectations for medical school leaders: a textual analysis of career advertisements 2000–2004 cf. 2010–2014. Issue 1 (2nd January 2016) - Gorsky, Diane; MacLeod, Anna
ABSTRACT: Leadership norms and expectations are continually evolving in higher education. Medical education is no exception to that trend, but shifts over time are intangible and difficult to measure. To explore emerging changes, the authors conducted a textual analysis of published career advertisements from 2000–2004 and 2010–2014. While a number of common themes united both time frames, new expectations emerge over a relatively brief period of time. The language of contemporary career advertisements conveys a landscape of leadership that is more collaborative, transparent, community-centred, accountable and team-based. This shift is significant, but perhaps less provocative than the absent discourses and contradictions. Despite the new leadership profile in 2010–2014, there is no mention of the important change management role required to guide organisational changes underway. Another contradiction relates to credentials. The contemporary advertisements fail to convey an updated career pathway and skill preparation aligned with the new leadership demands.